Fecal Viral Diversity of Captive and Wild Tasmanian Devils Characterized Using Virion-Enriched Metagenomics and Metatranscriptomics - Chong, Rowena; Shi, Mang; Grueber, Catherine E; Holmes, Edward C; Hogg, Carolyn J; Belov, Katherine; Barrs, Vanessa R (Journal of virology, 2019)
The Tasmanian devil is an endangered carnivorous marsupial threatened by devil facial tumor disease (DFTD). While research on DFTD has been extensive, little is known about viruses in devils and whether any are of potential conservation relevance for this endangered species. Using both metagenomics based on virion enrichment and sequence-independent amplification (virion-enriched metagenomics) and metatranscriptomics based on bulk RNA sequencing, we characterized and compared the fecal viromes of captive and wild devils. A total of 54 fecal samples collected from two captive and four wild populations were processed for virome characterization using both approaches. In total, 24 novel marsupial-related viruses, comprising a sapelovirus, astroviruses, rotaviruses, picobirnaviruses, parvoviruses, papillomaviruses, polyomaviruses, and a gammaherpesvirus, were identified, as well as known mammalian pathogens such as rabbit hemorrhagic disease virus 2. Captive devils showed significantly lower viral diversity than wild devils. Comparison of the two virus discovery approaches revealed substantial differences in the number and types of viruses detected, with metatranscriptomics better suited for RNA viruses and virion-enriched metagenomics largely identifying more DNA viruses. Thus, the viral communities revealed by virion-enriched metagenomics and metatranscriptomics were not interchangeable and neither approach was able to detect all viruses present. An integrated approach using both virion-enriched metagenomics and metatranscriptomics constitutes a powerful tool for obtaining a complete overview of both the taxonomic and functional profiles of viral communities within a sample. The Tasmanian devil is an iconic Australian marsupial that has suffered an 80% population decline due to a contagious cancer, devil facial tumor disease, along with other threats. Until now, viral discovery in this species has been confined to one gammaherpesvirus (dasyurid herpesvirus 2 [DaHV-2]), for which captivity was identified as a significant risk factor. Our discovery of 24 novel marsupial-associated RNA and DNA viruses, and that viral diversity is lower in captive than in wild devils, has greatly expanded our knowledge of gut-associated viruses in devils and provides important baseline information that will contribute to the conservation and captive management of this endangered species. Our results also revealed that a combination of virion-enriched metagenomics and metatranscriptomics may be a more comprehensive approach for virome characterization than either method alone. Our results thus provide a springboard for continuous improvements in the way we study complex viral communities.